A novel missense variant of HS6ST2 gene in Paganini-Miozzo syndrome with a rare neurodevelopmental and Endocrine phenotypes - Zhang, Meiling; Chang, Xiao; Du, Xiaoyun; Chen, Zhen; Zhang, Xinyue; Cai, Fucheng (Frontiers in Genetics, 2025)
Paganini-Miozzo syndrome (MRXSPM) is a globally rare disease caused by hemizygous mutations in the HS6ST2 gene on chromosome Xq26. This study presents the first case of MRXSPM in China, meanwhile the fourth case worldwide. The proband was admitted to the hospital due to developmental delay. Whole exome sequencing (WES) revealed a novel variant, c.764C>A (p.Pro255Glu) missense mutation in the HS6ST2 gene. Brain CT showed mild lateral ventricular enlargement, and electroencephalogram showed diffuse spikes and waves. Biochemical tests indicated significantly elevated transaminases, blood lactate values, and lactate/pyruvate values. Bioinformatics predictions suggest that this mutation may affect the thermal stability of the HS6ST2 protein. The amino acid where the mutation c.764C>A p.P255Q occurs is conserved across multiple species, specifically being proline in 13 species. In vitro cell experiments demonstrated that this mutant can impact the expression of HS6ST2 protein at post-transcriptional level. Comparison with previously reported cases revealed that different mutations might lead to different alternations in the function of HS6ST2 protein, resulting in distinct clinical phenotypes.